(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Checking the humidity meters means that the metrologist determines its true error and draws a conclusion about the suitability of this device for use. Since most moisture meters are based on indirect measurement methods, the most important task is its high-quality grading, i.e., to create a functional relationship between a certain amount and the moisture content of that material.